Reliability and Validity of the 50-ft Walk Test for Idiopathic Toe Walking. Issue 3 (July 2017) - Christensen, Catie; Haddad, Amanda; Maus, Elizabeth
Abstract : Purpose: To evaluate interrater reliability and concurrent validity of the 50-ft walk test (FWT) for children with idiopathic toe walking (ITW). Methods: Thirty children, 6 to 13 years old, with ITW participated. During the 50-FWT, an accelerometer counted total steps. A physical therapist counted the number of toe-walking steps. The number of toe-walking steps was divided by the total steps to calculate a toe-walking percentage. Interrater reliability was assessed by correlating the toe-walking percentage obtained by 2 raters using an intraclass correlation coefficient. Concurrent validity was evaluated by correlating the toe-walking percentage calculated by the GAITRite and therapist using a Spearman ρ. Results: There was excellent interrater reliability and concurrent validity. Experience level did not impact the therapist's ability to identify a toe-walking step. Conclusions: The 50-FWT demonstrated excellent interrater reliability and concurrent validity. It can be used to obtain a percentage of toe walking in children 6-13 years of age with ITW. Abstract : Evaluation of inter-rater reliability and concurrent validity of the 50-foot walk test for children with idiopathic toe walking.